Social Identity Change During an Intergroup Merger: The Role of Status, Similarity, and Identity Threat - Amiot, C.; Terry, Deborah; McKimme, B. (Psychology Press, 2012)
Conducted during the merger between two hospitals, this longitudinal study (N = 149) revealed that at both Time 1 (i.e., questionnaire completed 12 months prior to the merger) and Time 2 (completed 1 year after the merger had been implemented), employees from the low-status premerger organization generally reported lower adjustment to the merger. Whereas Time 2 identity threat predicted lower and decreased identification with the new merged organization and perceptions of a common in group identity, perceived similarities between the merging organizations at Time 2 predicted higher identification with the new merged organization and higher perceptions of a common in group identity.